MALDI-imaging enables direct observation of kinetic and thermodynamic products of mixed peptide fiber assembly. Issue 10 (19th January 2017) - Medini, Karima; West, Brandi; Williams, David E.; Brimble, Margaret A.; Gerrard, Juliet A.
Abstract : The first use of MALDI-imaging, as a snapshot tool to characterize multicomponent self-assembling peptide fibers. Abstract : Controlling the self-assembly of multicomponent systems provides a key to designing new materials and understanding the molecular complexity of biology. Here, we demonstrate the first use of MALDI-imaging to characterize a multicomponent self-assembling peptide fiber. Observations of mixed peptide systems over time demonstrate how simple sequence variation can change the balance between kinetic and thermodynamic products.